Making amends for negligence (BMJ Publishing Group, 2004)

(untitled)
That doctors are more likely to be sued for negligence now than they have been in the past is undeniable. In particular, in the 1980s and 1990s the number of claims steadily increased, relative to the number of treatment episodes. The reasons for this are by no means clear but probably include elements of a cultural shift in attitudes to the medical profession and the growth of the legal services “industry.” More contentious, however, is whether this change represents a good or a bad thing, and what if anything needs to be done about it. The chief medical officer’s consultation paper, “Making Amends,” starts from a premise that something does need to be done, and it puts forward suggestions for reform, including fast track arrangements for smaller cases, but stopping short of a full no fault scheme for all patients.1 Two contributors to this issue have reacted to the chief medical officer’s document somewhat critically. Brian Capstick maintains that the proposals for reform run the risk of increasing the burden on clinicians and hospital managers because the number of claims will increase and that therefore costs may be prohibitive.2 Bertie Leigh in his commentary argues that there is no real crisis in the current system—costs are under control, and and claims are dealt with proficiently on the whole.